Spatial and temporal patterns of bryozoan distribution and diversity in the Scottish sea regions. (19th September 2013) - Rouse, Sally; Spencer Jones, Mary E.; Porter, Joanne S.
Abstract: Diversity and distribution patterns of sessile benthic fauna over space and time are often incompletely known. Understanding the factors that govern these patterns is important for informing marine spatial planning, and monitoring the impacts of climate change and habitat alteration in the marine environment. Historical and contemporary records of bryozoans from Scotland were mapped to produce a GIS distribution layer and were assessed in conjunction with JNCC GIS benthic habitat layers. Bryozoans have predominantly been recorded from the west coast, Orkney, Shetland and Western Isle archipelagos. The greatest number of bryozoan species occurred in high energy, rocky environments; few species have been identified from the continental slope, which also has the least number of records. The biodiversity, as measured by the average taxonomic distinctness and variation in taxonomic distinctness, was assessed for sampling sites and sub‐regions within Scotland. High values were concentrated around the Orkney Isles and Southwest Scotland. This is the first known attempt at a comprehensive analysis of changes in Northern European bryozoan diversity and distribution from the 1700s through to the present day, but overall temporal patterns remain uncertain due to differences in the availability of records through time. This study provides an example of the application of methods that may be used to assess benthic diversity to identify potential sites for marine conservation or marine protected areas. As benthic data layers improve, and sampling is extended to unstudied areas, greater insight into the relationship between the physical environment and diversity and distribution patterns of benthic fauna will be gained. This study serves as a baseline for long‐term monitoring of biodiversity changes in this poorly studied Phylum.